Mary Poppins - Sherman, Richard M. 1928-2024; Sherman, Robert B. 1925-2012 (Walt Disney Home Entertainment, 2004)
After a banker's children lose their nanny due to her frustration with them, a change in the wind blows in a magical nanny who matches the children's qualifications, but not those of their very proper father. As Mary Poppins helps the children magically explore the world around them, their father grows increasingly disapproving of her methods, and he must eventually deal with his own distance from his children
Based on the "Mary Poppins" books by P.L. Travers
Originally produced as a motion picture in 1964
Title from container
Originally released as a motion picture in 1964
Keywords: Travers, P. L. / (Pamela Lyndon) / 1899-1996 / Film adaptations; Poppins, Mary / (Fictitious character) / Drama; Nannies / England / London / Drama; Father and child / England / London / Drama; Friendship / England / London / Drama; Poppins, Mary (Fictitious character) / Drama; Fantasy; Poppins, Mary (Personaje literario) / Teatro; Padres e hijos / Inglaterra / Londres / Teatro; Travers, P. L. / (Pamela Lyndon) / 1899-1996; Poppins, Mary / (Fictitious character); Father and child; Friendship; Nannies; England / London; DVDs; Feature; Children's films; Juvenile works; Animated films; Drama; Fantasy films; Feature films; Fiction films; Film adaptations; Films for the hearing impaired; Live-action/animation films; Musical films; Video recordings for the hearing impaired; Family / Feature; Musical / Feature; Film; DVD-Video